(untitled) (MASKAY, 2014)
This paper proposes an algorithm to be used for designing BitTorrent-based protocol pair selection policies, considering multimedia applications such as on-demand streaming and interactive scenarios. To do this, the interactive behavior of the client when accessing natural multimedia systems is analyzed. This analysis examines workloads from actual content providers and evaluates three critical parameters: temporal dispersion, spatial dispersion, and media object position popularity. These parameters are used as the foremost guidelines for writing the algorithm. Finally, the conclusion of this article draws on the challenges and possible future work in this field of research.